Pemidanaan Kerja Sosial Dalam Perspektif Pembaharuan Hukum Lalu Lintas Di Indonesia - Galih Puji Mulyono; Latifah (Fakultas Hukum Universitas Islam Malang, 2023)
The main punishment that is always formulated as a criminal threat for all types crimes, such as traffic accidents due to negligence, is imprisonment, although in its own development it is considered ineffective in realizing the goals of punishment. The research method used is normative legal research with a statutory approach and a conceptual approach. Social work punishment is an effective alternative punishment to make the perpetrators of a crime deterrent, which will not only provide legal certainty but also a sense of justice and benefit for both perpetrators and victims. Thus, the imposition of social work punishment is used as a form of protection for the human rights possessed by perpetrators, especially in traffic accident crimes due to negligence. Therefore, the final results of this study formulate social work punishment for perpetrators of traffic accident crimes due to negligence which is very appropriate when associated with criminal law reform.